УМОВИ ПІДВИЩЕННЯ ЯКОСТІ ДІЯЛЬНОСТІ МЕТОДИЧНОЇ СЛУЖБИ СЕРЕДНЬОЇ І ВИЩОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2007)
The article is devoted to the issue of improving the professional skills of the pedagogical staff, where a person and it's (his or her) own potential is of particular importance. The conditions of improvement are presented in the article.